Rehabilitation and Reentry: Addressing the Challenges of Incarceration and Recidivism in the United States - Nawaz, Ali; Yaseen, Abid; Zhaira, Dua; Khalid, Maryam (Journal of Neonatal Surgery, 2025)
Background: The United States maintains the highest incarceration rates among high-income nations, creating persistent social and health disparities. Despite the presence of rehabilitation and reentry programs, recidivism remains a major concern, reflecting gaps in existing interventions. Methods: Using a mixed-methods design, this study analyzed Bureau of Justice Statistics’ recidivism data (2005–2018) alongside semi-structured interviews with 40 participants, including formerly incarcerated individuals and reentry professionals. Quantitative analysis examined the impact of educational and vocational participation on reoffending, while qualitative insights captured lived experiences of reintegration. Results: Findings showed that participation in both educational and vocational programs significantly reduced recidivism rates, with dual-program engagement yielding the strongest protective effect. Interviews revealed the transformative role of education in fostering confidence, while barriers such as employment discrimination, housing instability, and stigma continued to impede reintegration. Conclusion: Rehabilitation and reentry efforts are most effective when implemented holistically, addressing both practical skills and emotional resilience. Expanding access to integrated education and vocational programs, coupled with supportive networks, can strengthen reintegration and reduce long-term recidivism.